AB0216 Effects of anti-citrullinated protein antibodies on systemic bone mass in rheumatoid arthritis patients. (15th June 2017) - Orsolini, G; Caimmi, C; Viapiana, O; Idolazzi, L; Fracassi, E; Gatti, D; Adami, G; Rossini, M
Abstract : Background: Bone loss in rheumatoid arthritis (RA) is a key feature both local and systemic. Anti-citrullinated protein antibodies (ACPA) have recently been found to directly induce differentiation and activation of osteoclasts and therefore contribute to periarticular bone loss. Objectives: The aim of this study was to analyze the effect of ACPA on systemic bone mineral density (BMD) in patients with established RA. Methods: This is a cross-sectional study with a single-center RA population. BMD was measured with Dual X-ray absorptiometry at lumbar and femoral sites. ACPA were measured by EIA. Multivariate analysis was performed adjusting for the main confounding variables. Results: One hundred twenty-seven RA patients were enrolled. In univariate analysis ACPA-positive patients showed lower BMD Z-score (SD below the age- and gendermatched mean reference value) at femoral sites (p<0.01). A negative correlation between ACPA titer and BMD Z-score at all sites was observed (p<0.01). The multivariate analysis adjusted for the main confounding variables confirmed the negative effect of ACPA at femoral sites (p<0.05), but not at lumbar spine BMD. No significant effect of rheumatoid factor has been observed. Conclusions: ACPA have a negative titer-dependent effect on BMD at femoral sites, mainly constituted by cortical bone. ACPA-positive patients, especially if at high titer, should undergo bone investigations and be treated with bone protecting agents. Disease-modifying anti-rheumatic drugs lowering ACPA titer might have positive effects on systemic bone mass. Disclosure of Interest: None declared